2021
DOI: 10.1108/lht-08-2021-0252
|View full text |Cite
|
Sign up to set email alerts
|

Infoecology of the deep learning and smart manufacturing: thematic and concept interactions

Abstract: PurposeThis infecological study mainly aimed to know the thematic and conceptual relationship in published papers in deep learning (DL) and smart manufacturing (SM).Design/methodology/approachThe research methodology has specific research objectives based on the type and method of research, data analysis tools. In general, description methods are applied by Web of Science (WoS) analysis tools and Voyant tools as a web-based reading and analysis environment for digital texts. The Yewno tool is applied to draw a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Asemi et al (2022a) presented a fully automated usability evaluation method for interactive social robots by a fuzzy inference system based on ISO 9241-210:2019. Asemi et al (2022b) studied the thematic and conceptual relationship in published papers on deep learning and smart manufacturing and its possible implications. Next, Agarwal et al (2022) reviewed the literature on chatbots and virtual assistants, which showed that this area has been increasing in the last few years.…”
Section: Prefacementioning
confidence: 99%
“…Asemi et al (2022a) presented a fully automated usability evaluation method for interactive social robots by a fuzzy inference system based on ISO 9241-210:2019. Asemi et al (2022b) studied the thematic and conceptual relationship in published papers on deep learning and smart manufacturing and its possible implications. Next, Agarwal et al (2022) reviewed the literature on chatbots and virtual assistants, which showed that this area has been increasing in the last few years.…”
Section: Prefacementioning
confidence: 99%
“…Research on scientific knowledge mapping originated in the field of information visualization, which mainly reveals the structure, evolution and cross-fertilization process of scientific knowledge by mining the intrinsic connections and dynamic evolution of literature data ( 2 ). With the rapid development of big data and artificial intelligence technology, the application scope of these methods are constantly expanding ( 3 ). In particular, the emergence of tools such as CiteSpace ( 2 ), VOSviewer ( 2 ), Pajek ( 4 ), and R-tool ( 5 ) has led to the widespread application of scientific knowledge mapping technologies in many disciplines, which provides new perspectives for researchers to understand in depth the development of disciplines and cutting-edge dynamics.…”
Section: Introductionmentioning
confidence: 99%